The Influence of Environmental Knowledge, Place Attachment, and Ecoliteracy on Pro-Environmental Behavior of Class X and XII Students at SMA N 1 Sitiung - Nova Yulfiana Sari; Nefilinda; Momon Dt Tanamir (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to analyze and describe the influence of environmental knowledge, place attachment and ecoliteracy on the pro-environmental behavior of class X and XI students at SMA N 1 Sitiung and the influence of environmental knowledge, place attachment and ecoliteracy together on the pro-environmental behavior of class X and at SMA N 1 Sitiung. The sample collection technique in the research that the researcher will carry out is using a probability sampling technique, namely Proportionate stratified random sampling. Research results: 1). There is a positive and significant influence between environmental knowledge on pro-environmental behavior, namely the t value is 3.756 while the p value is 0.000, so the p value is <5% (0.000 <0.05). 2). There is a positive and significant influence between place attachment on pro-environmental behavior, namely with a t value of 7,820, while the p value is 0.000, so the p value is <5% (0.000 <0.05).